1995
DOI: 10.1111/j.1151-2916.1995.tb08434.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Ceramic Materials in Microwave Heating

Abstract: Thermal stability was examined theoretically for various commercial grades of alumina heated by microwave energy. The critical temperature for thermal runaway was evaluated as a function of Biot number and ambient temperature, employing various functional forms of the dependence of dielectric loss with temperature. Field‐temperature relationships were derived for the limit of small temperature gradients in the specimen. Finite difference methods were used under conditions where significant temperature gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 9 publications
0
29
0
6
Order By: Relevance
“…Firstly, most of the research on material processing by microwaves is based on conventional low-frequency (2.45 GHz) microwave applicators; however, such applicators do not couple microwave power efficiently to many materials at room temperature and poor microwave absorption characteristics make initial heating difficult [21]. Secondly, thermal instabilities may occur, which can lead to the phenomenon of temperature runaway [21]; i.e., the specimen overheats catastrophically. This occurs for a wide vari- Fig.…”
Section: Two Directional Microwave Heating (Microwave Hybrid Heating)mentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, most of the research on material processing by microwaves is based on conventional low-frequency (2.45 GHz) microwave applicators; however, such applicators do not couple microwave power efficiently to many materials at room temperature and poor microwave absorption characteristics make initial heating difficult [21]. Secondly, thermal instabilities may occur, which can lead to the phenomenon of temperature runaway [21]; i.e., the specimen overheats catastrophically. This occurs for a wide vari- Fig.…”
Section: Two Directional Microwave Heating (Microwave Hybrid Heating)mentioning
confidence: 99%
“…During sintering materials by direct microwave heating, various fundamental problems are usually encountered [21]. Firstly, most of the research on material processing by microwaves is based on conventional low-frequency (2.45 GHz) microwave applicators; however, such applicators do not couple microwave power efficiently to many materials at room temperature and poor microwave absorption characteristics make initial heating difficult [21].…”
Section: Two Directional Microwave Heating (Microwave Hybrid Heating)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have also demonstrated carbon as preheating source [20]. Some authors like Spotz et al have also reported LaCrO 3 and mixture of Al 2 O 3 +LaCrO 3 as suitable susceptor materials for certain applications [21]. P.D.…”
Section: Introductionmentioning
confidence: 96%
“…), and was a serious problem in the processing of materials whose dielectric properties are abruptly altered with rising temperature. Studies (Spotz et al, 1995) demonstrated that the insulation normally used to contain heat inside the cavity can exacerbate the problem of thermal runaway. However, the data also suggested that thermal runaway may be minimized or controlled by hybrid heating, thus allowing low-loss ceramic materials to be processed using rapid firing.…”
Section: Microwave Fast Sintering Of Ceramicsmentioning
confidence: 99%